Analisis Soal Ulangan Harian pada Materi Perubahan Lingkungan di Kelas X SMA di Kota Padang (Jurnal Bioconcetta, 2017)
One of the causes of student learning outcomes are less is that evaluation tools used are too difficult. This study aims to provide information about the validity, reliability, index of difficulties, and differentiation of the matter of test. The type of this research is descriptive research. Based on the results of the analysis of the validity of the question of daily test of environmental change material, obtained validity value with the criteria of validity is very high, the reliability value with the criteria of reliability is very high, the problem of trouble index analysis there are 6 questions including difficult question, 64 problem including moderate, and 13 problem including easy, with criteria of index of difficulty of problem is on medium criterion, result of different power about 4 problem with bad criterion once, 24 questions with poor criteria, 46 questions with moderate criteria and 9 questions with good criteria. It can be concluded from the result of daily item test analysis on the 1st years senior high school in Padang City Environmental Change material in Padang City Lesson Year 2016/2017 in terms of validity, reliability, difficulty index has show the criteria of a good question, but the question of different potency does not show the criteria of a good question.